THE EFFECT OF ORGANIZATIONAL CULTURE TOWARDS ORGANIZATIONAL PERFORMANCE AT DINAS PERINDUSTRIAN DAN PERDAGANGAN PROVINSI SULAWESI UTARA (DISPERINDAG) - Sengke, Gerald (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2015)
Culture have a big influence on organizations performance in the world-wide. Absolutly all the organizations have their own culture. The organizational culture like competitive culture, entrepreneurial culture, bureaucratic culture and consensual culture has an effect on organizational performance. The objectives of the study is to know the effect of the organizational culture towards organizational performance at Disperindag Sulut. Data was analyzed quantitatively and through use of statistical package for social scientists (SPSS). The research method is multiple regression analysis using saturated sampling with the sample of the respondents is 98 samples of all the employees at Disperindag. The result of this study shown that organizational culture has a great effect on organizational performance. consensual culture, competitive culture and bureaucratic culture have a significant effects on organizational performance. The employees on Â Disperindag prefer to seek work environment that can improve performance by having team building initiatives to help enhance team spirit within the organization. while entrepreneurial culture is needs to be strengthened for the employee to become creative and innovative for the better performance. Keywords: organizational culture, competitive, entrepreneurial, bureaucratic, organizational performance